Dielectric Elastomers in Actuation and Energy Applications: Material Behavior and Design Strategies - Sai Preetham Anumasu (International Journal of Electro-Mechanics and Material Behaviour, 2025)
Dielectric elastomers (DEs), a class of electroactive polymers, have attracted significant attention for their ability to undergo large, reversible deformations under electric stimulation. This unique capability makes them highly suitable for a range of actuation and energy harvesting applications, especially in the emerging fields of soft robotics, flexible electronics, artificial muscles, and sustainable power generation systems. DEs offer compelling advantages such as low weight, mechanical flexibility, high energy density, and silent operation. Their electromechanical performance, however, is strongly influenced by intrinsic material properties, electrode compatibility, and external operating conditions. This review presents a comprehensive exploration of the fundamental material behavior of dielectric elastomers, including their electromechanical coupling mechanisms, hyperelastic modeling, and major failure modes such as electrical breakdown and mechanical fatigue. A detailed comparison of commonly used materials, such as acrylics and silicones, is provided alongside emerging nanocomposites and hybrid structures designed to enhance dielectric strength, stretchability, and energy conversion efficiency. The article also discusses essential design strategies for developing reliable DE-based devices. These include the choice of compliant electrodes, pre-straining techniques, multilayer configurations, and optimized geometries that maximize actuation force and energy output. Special attention is given to innovations in low-voltage operation, self-healing materials, and integrated sensing capabilities. In the context of energy applications, the principles and performance of dielectric elastomer generators (DEGs) are examined, highlighting their potential for wearable, biomechanical, and environmental energy harvesting. Despite recent progress, challenges remain in the scalable fabrication, long-term durability, and high-voltage operation of DE systems. The review concludes with an outlook on future research directions aimed at overcoming these limitations and achieving seamless integration of DEs into next-generation adaptive systems. Through this multidisciplinary approach, dielectric elastomers are poised to transform the landscape of smart materials and flexible electromechanical technologies.
Keywords: Dielectric elastomers; Energy harvesting; artificial muscles; dielectric breakdown; electroactive polymers; electromechanical modelling; nanocomposites; soft actuators